Uji Simulasi Keretakan Telur dengan Alat Guncangan (Getaran) - Hanif, Anwar; Tamrin, Tamrin; Kuncoro, Sapto; Zulkarnain, Iskandar (abe.fp.unila.ac.id, 2023)
Eggs are livestock products that contribute greatly to the adequacy of community nutrition. . The egg composition physically consists of 10% shells (eggshells /shells), 60% egg whites, and 30% egg yolks. The purpose of this study is to test a simulation tool for egg transportation based on the amount of vibration, number of stacks and type of egg container on egg quality. a standard deviation test is performed. The results of this study showed the average physical characteristics of chicken eggs measured by 57.6 mm for the longest diameter, 44.8 mm for the shortest diameter, 63.9 grams for weight, 66.8 ml for volume, and 0.96 for density. The average physical characteristics of duck eggs measured were 57.1 mm for the longest diameter, 45.9 mm for the shortest diameter, 67 grams for weight, 69.8 ml for volume, and 0.96 for density. The average physical characteristics of quail eggs measured were 31.9 mm for the longest diameter, 24.9 mm for the shortest diameter, 10.7 grams for weight, 60.2 ml for volume, and 0.18 for density, No. there are broken eggs when dropped at a height of 5 to 20 cm from the ground surface while at a height of 25 cm there are broken eggs as many as 9.38% of the total sample for chicken eggs. Mechanical vibrations of eggs at an amplitude of 5 cm with a rotational speed of 40 rpm, 60 rpm and 76 rpm for 20 minutes do not result. mechanical damage to chicken eggs, duck eggs and quail eggs in the form of cracks or broken. Keywords: eggs, Simulation tools.